H16 Implementing and assessing the use of mindfulness sessions in a specialist UK HD hospital: a service evaluation. (12th September 2022) - Jones, Lee; Dale, Maria
Abstract : Background: People with HD (pwHD) often experience a range of psychological difficulties, which contribute to reduced quality of life. Mindfulness-based approaches are psychological interventions that involve bringing attention to the present moment, without judgement. Research among other neurological populations, has shown beneficial effects of mindfulness across several outcomes including quality of life, depression, anxiety, fatigue, and sleep. Although mindfulness-based interventions are in their infancy among pwHD, they show promise, with some HD participants reporting an increased sense of calm and improved emotion regulation. Aims: This project aims to implement and evaluate a six-week program of weekly mindfulness sessions in a specialist HD hospital in the UK. Methods/Techniques: This service evaluation will assess weekly mindfulness sessions, delivered both in small groups and on a one-to-one basis, among people with moderate to late-stage HD. Before and after each session, participants will: be assessed using a modified Interact Short Form, complete an adapted version of the visual analogue mood states (VAMS) to assess levels of anxiety and relaxation, and report how much they enjoyed the session using Likert scales. For those able to engage, a semi-structured interview will be undertaken on a one-to-one basis at the end of the six-week program. Results: The intervention is ongoing, but initial patient and staff feedback has been favourable. Conclusions: Mindfulness sessions have been found to improve several clinical outcomes among different neurological populations. Therefore, we anticipate that HD inpatients with moderate to advanced HD will find this approach beneficial, as an addition to their usual care.